Fabrication of polyglutamic acid-based sensor for electrochemical determination of a phenicol antibiotic in water environment - Nguyen, Thi Kim Ngan; Vu, Thi Thu Ha; Dang, Van Thanh; Nguyen, Tra My; Pham, Thi-Hai Yen (Vietnam Journal of Science and Technology, 2023)
In this study, a graphite electrode (GrE) modified with polyglutamic acid was used to determine chloramphenicol (CAP), a phenicol antibiotic, in a water environment using adsorptive stripping linear sweep voltammetry. The pGA modification process involved electropolymerization via cyclic voltammetry, resulting in a significantly enlarged electrochemical active area of the pGA/GrE interface (1.5 times greater than that of the unmodified GrE). The highest CAP signal was obtained on the electrode fabricated by scanning 50 cycles in the potential range of -1.2 V to +2.0 V. The CAP signal recorded on the pGA/GrE electrode was nine times higher than that on the GrE, which was due to the larger electrochemical active area of the pGA/GrE and its good adsorption capacity with CAP. Analysis conditions including the pH of electrolyte and accumulation time, were optimized. Under optimal conditions, the calibration curve was built with two linear regions in the concentration ranges of 0.5-20 µmol L-1 (R2 = 0.987) and 20-100 µmol L-1 (R2 = 0.996), and the detection limit for CAP was 0.28 µmol L-1.